Chorebus (Phaenolexis) sakhalinicus TOBIAS 1998 ... - Papp, J. (Zenodo, 2007)
Chorebus (Phaenolexis) sakhalinicus TOBIAS, 1998 – 1 ♂: KU 22. – Described by 1 ♀ + 1 ♂ from Sakhalin. New to the fauna of Korea. – Antenna with 43 antennomeres, hind tibia and tarsus equal in length, first tergite 2.3 times length of hind breadth. ... : Published as part of Papp, J., 2007, Braconidae (Hymenoptera) From Korea Xxii. Subfamily Alysiinae, pp. 1-38 in Acta Zoologica Academiae Scientiarum Hungaricae 53 (1) on page 9, DOI: 10.5281/zenodo.5731826 ...